2018
DOI: 10.4103/jcd.jcd_406_16
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ultrasonics on the penetration depth of AH plus, acroseal, and EndoREZ root canal sealers: An in vitro study

Abstract: Aim:The aim of this study is to evaluate the effect of ultrasonic activation on the penetration depth of AH Plus, Acroseal, and EndoREZ sealers into dentinal tubules using Confocal laser microscopy.Methods:A total of 60 single-rooted teeth were prepared and divided into three groups on the basis of the type of sealer used (G1: AH Plus, G2: Acroseal and G3:EndoREZ). Each group was further subdivided into two equal subgroups on the basis of ultrasonic activation of sealers and nonactivation. Teeth were obturated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Recent studies that investigated the influence of ultrasonic activation on the tubular penetration presented conflicting results [4][5][6][8][9][10][11][12]. Accordingly, in some studies, ultrasonic activation was found to increase sealer penetration [5,6,[8][9][10][11][12], while in other studies, no significant effect was reported [4,9,10]. There are also studies reporting that ultrasonic activation resulted in increased tubular penetration depending on the sealer type [9,10].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent studies that investigated the influence of ultrasonic activation on the tubular penetration presented conflicting results [4][5][6][8][9][10][11][12]. Accordingly, in some studies, ultrasonic activation was found to increase sealer penetration [5,6,[8][9][10][11][12], while in other studies, no significant effect was reported [4,9,10]. There are also studies reporting that ultrasonic activation resulted in increased tubular penetration depending on the sealer type [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…The sealer placement technique can affect the quality of obturation [4][5][6][7]. Sealers can also be activated during placement for better penetration to the canal irregularities and dentin tubules [8][9][10][11][12]. The activation is generally performed with several sonic or ultrasonic tips connected to their specific equipment which produce high frequency of oscillations [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The master gutta-percha coating technique is the simplest method and was adopted in the present study, since it requires no additional instruments and procedures. Recent studies found that the depth of sealer penetration is influenced by the type of placement technique and by the root canal level (13,14). However, some previous studies revealed that sealer distribution along canal walls was not influenced by the sealer placement technique (15).…”
Section: Discussionmentioning
confidence: 99%